Experimental study on the hydraulic performance of nonwoven geotextile as subsurface drain filter in a silty loam area - Mohamed Monir Elzoghby (Elsevier, 2021)
Synthetic geotextile envelope can be used as a replacement of sand filters for subsurface drainage pipes. However, clogging and blocking can occur if the filter does not match the soils properly. This paper presents a laboratory study on hydraulic performance of nonwoven geotextile as subsurface drain filter for silty loam soil in eastern China. Two selected synthetic geotextiles were tested. Results showed that Typar SF27 satisfied the filtration requirements compared to the traditional sand filters. Typar SF20 exhibited a clogging risk of about 50% more than SF27; it also exposed to soil loss about 10 times more than SF27. The results indicate that choosing geotextile envelope material for the targeted soils need to consider O90 of the geotextile material and soil size distribution. Findings from this study may provide technical reference for selecting proper geotextile filtering material for subsurface drainage pipes in the study area and regions with similar soil conditions.